ANALISIS PENGARUH STRUKTUR MODAL, PERTUMBUHAN PENJUALAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Perusahaan Real Estate dan Properti yang Terdaftar di BEI Tahun 2010-2014) - Limbong, Dita Tessa Sampriani; Chabachib, Mochammad (Diponegoro Journal of Management, 2016)
This research aims to analyze the effect of capital structure (DER), sales growth, and firm size of firm value (PBV) and profitability (ROE) as an intervening variable. The data used in this study were obtained from financial statements of the real estate and property company that is listed on the Indonesia Stock Exchange in 2010-2014. This study uses secondary data. The selection of the sample using a purposive sampling tecnique and using 32 companies. The analysis technique used is Path Analyst which is a development of the bivariate and multiple regression analysis.The results of this study showed that capital structure and growth sales have a positive effect and significant to probability, firm size has a negative effect and insignificant Â to profitability. Probability and capital structure have a positive effect and significant to firm value. Growth Â Sales and firm size have a negative effect and insignificant to firm value. Profitability is able to mediate the effect of capital structure and growth sales on firm value. But profitability is not able to mediate the effect of firm size on firm value.